Fulminant Influenza A Myocarditis Complicated by Transient Ventricular Wall Thickening and Cardiac Tamponade - Milan Radovanovic; Igor Dumic; Charles W. Nordstrom; Richard D. Hanna (MDPI AG, 2022)
Myocarditis is an infrequent complication of influenza infection that is most often diagnosed clinically in the setting of confirmed influenza infection and elevated cardiac enzymes. Pericarditis can also occur in cases of influenza myocarditis and may require pericardiocentesis for tamponade. Patients with fulminant myocarditis have cardiogenic shock; however, echocardiographic findings may be subtle, showing a preserved ejection fraction and diffuse left ventricular wall thickening (compared to baseline) due to inflammatory edema. Recognizing these echocardiographic findings in the appropriate clinical setting facilitates the early recognition of fulminant myocarditis. Therefore, we report a case of fulminant influenza A myocarditis in healthy 37-year-old women complicated by transient left ventricular wall thickening and tamponade, highlighting the importance of early diagnosis and supportive management for a successful outcome.